2021
DOI: 10.1001/jamasurg.2021.0586
|View full text |Cite|
|
Sign up to set email alerts
|

Opportunities and Challenges for the Next Phase of Enhanced Recovery After Surgery

Abstract: ERAS) is a global surgical quality improvement initiative now firmly entrenched within the field of perioperative care. Although ERAS is associated with significant clinical outcome improvements and cost savings in numerous surgical specialties, several opportunities and challenges deserve further discussion.OBSERVATIONS Uptake and implementation of ERAS Society guidelines, together with ERAS-related research, have increased exponentially since the inception of the ERAS movement. Opportunities to further impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 120 publications
1
108
0
Order By: Relevance
“…Nevertheless, the implementation of the ERAS protocol in orthopedic practice remains a difficult issue [ 7 ]. Recently, a number of studies on ERAS have reported various obstacles in ERAS implementation, such as reduced compliance and ERAS protocol deviation by providers and patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the implementation of the ERAS protocol in orthopedic practice remains a difficult issue [ 7 ]. Recently, a number of studies on ERAS have reported various obstacles in ERAS implementation, such as reduced compliance and ERAS protocol deviation by providers and patients [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced Recovery After Surgery (ERAS) has become the new standard of perioperative care [ 18 , 19 ]. Furthermore, increased compliance to the evidence-based-multimodal system is strongly associated with better outcomes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate adoption of technology improves outcomes, but this has to be imbedded in a system that can evaluate the value proposition. 5,7,12 Avoidance of major complications should be the focus. They are miserable for the patient and reduce the quality and quantity of life.…”
Section: Appropriate Adoption Of Technologymentioning
confidence: 99%